2019
DOI: 10.1039/c8ta11452h
|View full text |Cite
|
Sign up to set email alerts
|

Janus membrane decorated via a versatile immersion-spray route: controllable stabilized oil/water emulsion separation satisfying industrial emission and purification criteria

Abstract: A PANI–SiNP-decorated Janus membrane was fabricated for highly efficient stabilized oil-in-water and water-in-oil emulsion separation, meeting industrial purification standards.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(39 citation statements)
references
References 35 publications
0
39
0
Order By: Relevance
“…On the other hand, membrane processes are considered a suitable and low-cost alternative to the conventional techniques for treatment of oilfield wastewater, due to unique properties such as the simples process, low energy consumption and no phase transformation [6,7]. Recent studies have reported the use of polymeric membranes for oily wastewater treatment [8][9][10]. Zhang, B. et al [11] reported the use of a polytetrafluoroethylene (PTFE) membrane for the study of the mechanisms of adsorption fouling of crude oil.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, membrane processes are considered a suitable and low-cost alternative to the conventional techniques for treatment of oilfield wastewater, due to unique properties such as the simples process, low energy consumption and no phase transformation [6,7]. Recent studies have reported the use of polymeric membranes for oily wastewater treatment [8][9][10]. Zhang, B. et al [11] reported the use of a polytetrafluoroethylene (PTFE) membrane for the study of the mechanisms of adsorption fouling of crude oil.…”
Section: Introductionmentioning
confidence: 99%
“…This substrate‐dependent issue could be addressed to some extent through the single‐side spraying technique. [ 71–78 ] The modifier solution is atomized with an airbrush for this method, and the fog droplets are accelerated to directionally impact the membrane surface. The further penetration of the modifier solution due to the capillary effect is to some extent reduced because of the very rapid spray process (in seconds) and comparative fog drop size with membrane pores.…”
Section: Asymmetric Surface Construction and Regulation For Janus Memmentioning
confidence: 99%
“…Compared with conventional membrane materials, the existence of "diode" phenomenon makes Janus membrane achieve higher separation e ciency and selectivity in oil/water separation (Li et al 2016;Wang et al 2017b). Such a "smart" property of Janus membrane with double-sided asymmetric property indicates great promise not only for oil/water separation (Liu et al 2017b(Liu et al , 2020Wang et al 2017a;An et al 2018;Lin et al 2019;Yao et al 2019;Zhang et al 2019;Zuo et al 2020)but also for water collection (Gao et al 2018), functional textiles (Dai et al 2019;Wang et al 2020), and other eld (Li et al 2020).…”
Section: Introductionmentioning
confidence: 99%